Designing Sodium Manganese Oxide with 4 d‐Cation Zr Doping as a High‐Rate‐Performance Cathode for Sodium‐Ion Batteries. Issue 12 (6th April 2020) - Shi, Wen‐Jing; Zheng, Ya‐Min; Meng, Xiao‐Meng; Liu, Shi‐Bin; Xu, Shou‐Dong; Chen, Liang; Wang, Xiao‐Min; Zhang, Ding
Abstract: Sodium‐ion batteries (SIBs) using transition‐metal oxides as cathodes have been considered as prospective alternatives for energy storage applications. Herein, the 4d‐cation Zr‐substitution strategy is proposed to optimize the structure and electrochemical properties of Na0.44 MnO2 for the first time. In situ X‐ray diffraction demonstrates that the optimized Na0.44 Mn0.98 Zr0.02 O2 exhibits a smaller volume change (only 4.25 %) during the initial charge/discharge process. Additionally, the Na + diffusion coefficients are significantly enhanced after Zr introduction, thus leading to superb rate properties. A high reversible capacity of 112 mAh g −1 can be obtained at 1 C. The long cycle lifespan can be supported by 78 mAh g −1 that is maintained after 1000 cycles with a capacity retention of 80 % at 5 C. These findings not only indicate that 4d‐cation Zr‐substitution is an effective approach to tune the tunnel‐type cathodes, but also provide a new avenue to devise and optimize high‐performance cathodes for SIBs. Abstract : Showing potential : A novel Na0.44 Mn0.98 Zr0.02 O2 cathode is designed by using the Zr‐substitution strategy. The effects of Zr doping on the structure and sodium storage performance are systematically investigated. The galvanostatic intermittent titration technique (GITT) and in situ XRD results indicate that Zr introduction significantly facilitates the Na + diffusion kinetics and decreases the volume change upon the electrode process, thus resulting in superior high‐rate performance and long cyclic stability.